Three-dimensional pore networks and transport properties of a shale gas formation determined from focused ion beam serial imaging. (1st January 2012) - Dewers, Thomas A.; Heath, Jason; Ewy, Russ; Duranti, Luca
Three-dimensional pore network reconstructions of mudstone properties are made using dual focused ion beam-scanning electron microscopy (FIB-SEM). Samples of Jurassic Haynesville Formation mudstone are examined with FIB-SEM and image analysis to determine pore properties, topology, and tortuosity. Resolvable pore morphologies (> 10 nm) include large slit-like pores between clay aggregates and smaller pores in strain shadows surrounding larger clastic grains. Mercury injection capillary pressure (MICP) data suggest a dominant 1–10 nm or less size of pores barely resolvable by FIB-SEM imaging. Computational fluid dynamics modelling is used to calculate single phase permeability of the larger pore networks on the order of a few nanodarcys (which compare favourably with core-scale permeability tests). This suggests a pore hierarchy wherein permeability may be limited by connected networks of inter-aggregate pores larger than about 20 nm, while MICP results reflect smaller connected networks of pores residing in the clay matrix. [Received: May 12, 2011; Accepted: September 14, 2011]